Combined laparoscopic abdominoperineal resection and robotic‐assisted prostatectomy for synchronous double cancer of the rectum and the prostate. Issue 2 (May 2016) - Kamiyama, Hirohiko; Sakamoto, Kazuhiro; China, Toshiyuki; Aoki, Jun; Niwa, Koichiro; Ishiyama, Shun; Takahashi, Makoto; Kojima, Yutaka; Goto, Michitoshi; Tomiki, Yuichi; Horie, Shigeo
Abstract: Here we report a combined laparoscopic abdominoperineal resection and robotic‐assisted prostatectomy. A 74‐year‐old man was diagnosed with T4b low rectal and prostate cancer. The operation was performed after neoadjuvant chemotherapy for the rectal cancer. The procedure used eight ports in total, five for laparoscopic abdominoperineal resection and six for robotic‐assisted prostatectomy. First, laparoscopic total mesorectal excision including division of the inferior mesenteric artery was performed, and then, robotic dissection of the prostate was performed. The en bloc specimen was removed through the perineal wound. Then, robotic urethrovesical anastomosis was performed. An extraperitoneal end colostomy was created to finish the operation. The operating time was 545 min, and blood loss was 170 mL. The postoperative course was uneventful, and the patient discharged on postoperative day 17. The combined laparoscopic abdominoperineal resection and robotic‐assisted prostatectomy were performed safely without any additional technical difficulty, as both procedures shared port settings and patient positions.